Profiles and Plotlines: Data Surveillance in Twenty-First Century Literature. By Katherine D. Johnston. U of Iowa P, 2023, 207 pp. - Joshua Parker (Journal of the Austrian Association for American Studies)
Joshua Parker reviews Katherine D. Johnston's Data Surveillance in Twenty-First Century Literature (U of Iowa P, 2023).